1960
DOI: 10.1111/j.1748-1716.1960.tb02075.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Training on Work Capacity, Total Hemoglobin, Blood Volume, Heart Volume and Pulse Rate in Recumbent and Upright Positions1

Abstract: HOLMGREN, A., F. MOSSFELDT, T. SJ~STRAND and G. STROM. Effect of training on work capacib, total hemoglobin, blood volume, heart volume and pulse rate in recumbent and upright positions. Acta physiol. scand. 1960. 50. 72-83.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1
1

Year Published

1967
1967
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(21 citation statements)
references
References 10 publications
3
16
1
1
Order By: Relevance
“…Similar results have been reported in subsequent investigations [18,27]. Findings from a large-scale, cross-sectional study indicated that athletes have a higher RBC than controls [25].…”
Section: Effects Of Exercise Training On the Erythrocytic Systemsupporting
confidence: 76%
See 1 more Smart Citation
“…Similar results have been reported in subsequent investigations [18,27]. Findings from a large-scale, cross-sectional study indicated that athletes have a higher RBC than controls [25].…”
Section: Effects Of Exercise Training On the Erythrocytic Systemsupporting
confidence: 76%
“…Blood volume represents the sum of erythrocyte volume and plasma volume. Erythrocyte volume and plasma volume can change independently of one another to alter the blood volume [8,17,18,19,20,21]. With endurance training, plasma volume expansion can occur rapidly over several hours to days, whereas erythrocyte volume expansion usually occurs slowly over many weeks to months [5].…”
Section: Effects Of Exercise Training On the Erythrocytic Systemmentioning
confidence: 99%
“…22 The conflicting results obtained in the present study may be due to differences in blood pressure of the subjects and the intensity of exercise. The volume and electrolyte responses to exercise training in essential hypertensive subjects may differ from that in normotensive subjects because of genetic abnormalities in body fluid and electrolyte homeostasis.…”
Section: Hemodynamic Effects and Humoral Responsescontrasting
confidence: 53%
“…The change in the plasma volume during exercise is rather conflicting,but it is generally accepted that a significant increase in plasma volume is induced by prolonged strenuous exercise (HOLMGREN et al,1960;OSCAI et al,1968).In the present study,the reduction of total hemoglobin during exercise period was observed in the anemic subjects,therefore,we may conclude that the concomitant reductions of hemoglobin concentration and hematocrit value in the anemic subjects are not only due to a result of hemodilution,but also to an absolute reduction of hemoglobin. Osmotic fragility of red cells increased from the third to the tenth days of the exercise period in the standard-and low-protein groups,but this phenomenon was not observed in the high-protein group.As the young red cells have a relative ability to resist hemolysis in hypotonic salt solutions (BisHoP,1964),an increase in reticulocytes may reduce osmotic fragility.This may partly explain the lack of the increase in the osmotic fragility of red cells in the high-protein group.As shown in Fig.4,the plasma level of hemoglobin increased after the exercise,and we may assume that the reduction of red cells during exercise is the result of intravascular hemolysis due to an increased susceptibility of red cells.The free hemoglobin in the plasma will be rapidly bound with haptoglobins (ALLISON and REES,1957).…”
Section: Discussionmentioning
confidence: 99%